Debt Management Performance Assessment : The Gambia - World Bank (Washington, DC, 2013)
During January 11 to 20, 2010, a World Bank team undertook a Debt Management Performance Assessment (DeMPA) mission to Gambia. This tool provides a methodology for assessing government debt management performance through a comprehensive set of dimensions spanning the full range of DeM functions. The first time the tool was applied in Gambia was in 2007, when a pilot study was carried out, and this was a follow-up mission. The DeMPA methodology has evolved since the report made in 2007 and therefore it is not possible to carry out a strict comparison of the two DeMPA reports in terms of individual indicators as the detailed dimensions that make up an indicator are no longer aggregated; instead, each dimension is given a specific score. It is clear however that Gambia's debt management has progressed substantially in some dimensions during recent years although there are still remaining issues that would benefit from reform and institutional capacity-building. The mission notes that given that several reforms are currently being implemented, it is to be expected that future DeMPA evaluations will show stronger scores. At this moment there is institutional capacity-building in the area of the Integrated Financial Management Information System (IFMIS) and cash management; the design of procedures manuals for Directorate of Debt Management (DDM), and the design of a draft bill on public debt management which would provide a more strategic, objectives-based legal orientation to debt management.